STRUCTURAL EVOLUTION AND HYDROCARBON PROCPECTIVITY OF KUBU HIGH, CENTRAL SUMATRA BASIN - HARRIS DARMAWAN , FITHRA
Activities of oil and gas exploration have started in Central Sumatra Basin since 1930 by Pacific Nederlandsche Petroleum Maatschappij (NPPM). Since exloration well Kubu-1 drilled by NPPM in 1939, exploratory drilling to find hydrocarbon reserves continue to do in Kubu High area. Until now drilling exploratory wells to find hydrocarbon accumulation in this area still has not shown encouraging results with the low success rate of exploration wells in Kubu High area. This study aims to understand the structural evolution of Kubu High in relation to hydrocarbon prospectivity in this area. Areas of study focused on Kubu High areas that have 2D migration seismic data covering an area of 40 km x 40 km. The interpretation of seismic data conducted on 40 lines of 2D seismic with a total length of approximately 500 km. The interpretation of seismic data performed by first tying well data to seismic data and then interpreted regional markers in Central Sumatra Basin. There are five regional markers interpreted in the study area, which are Telisa, Bekasap, Bangko, Menggala, and Basement. After horizon interpretation was done to all 2D seismic lines in the study area, further horizons flattening were done to see the structural evolution at the time of deposition of each horizon. Restoring the stratigraphic record before deformation can help in modelling the structure development in an area. Seismic image flattening attempts to reverse the effects of geologic processes by removing all of the geologic structure present in the image and thereby transforming the image into layers as they were deposited in geologic time. This method eliminates the influence of the structure and allows us to determine the geological conditions at the time of the deposited layer. The result of the study told that the basement in the study area which is the altitude and elevated position on the current conditions is a paleohigh and is not a product of F3 tectonic activity in Central Sumatra Basin. This opens up the possibility for a new exploration play in this area, which is fractured basement play on Kubu High. Basement at Kubu High is a paleohigh and remains as a high in its history since the Pre-Tertiary and has undergone multiple tectonic events for a long time. This condition allows fractures to develop well in Kubu High and make basement at Kubu High has a good potential to be a reservoir. Kubu High which a paleohigh has become the focal point of the hydrocarbon migration from the Late Miocene. The possibility of a new exploration play is expected to open a new paradigm in hydrocarbon exploration activities in Kubu area which has a very small success rate for hydrocarbon discoveries in Sihapas Group.